Molecular characterization of ornamental fosh (peocilidae) species by pcr-rflp of mitochondrial dna 12s rRNA gene - Azam, Mohamad Nor Fatihin Abshar Mohd Nor (Pusat Pengajian Kesihatan, 2015)
In this study four ornamental fish species from Peociliidae family namely Xiphophorus maculatus, Xiphophorus hellerii, Poecilia reticulate, Limia Vitatta and Poecilia shenops v/qtq used as a samples. Characterization of fish species was carried out by Polymerase chain reaction-restriction fragment length polymorphism (PCR-RFLP) followed by digestion with endonucleases restriction enzymes. Three different enzymes were used such as Alu I, Dde I and Mse I. Based on result only Xiphophorus maculatus showed species specific profile after treated with Alu I enzyme. No species specific was seen in all fish species after treated with Mse I and Dde I.